2020
DOI: 10.3390/agronomy10030337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementary Lighting Duration on Growth and Activity of Antioxidant Enzymes in Grafted Watermelon Seedlings

Abstract: Insufficient exposure to light in the winter may result in a longer production periods and lower quality of seedlings in greenhouses for plug growers. Supplementary artificial lighting to plug seedlings may be one solution to this problem. The objective of this study was to assess the effects of the duration of the supplementary light on the growth and development of two watermelon cultivars, ‘Speed’ and ‘Sambok Honey’ grafted onto ‘RS-Dongjanggun’ bottle gourd rootstocks (Lagenaria siceraria Stanld). Seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…Light is the foremost energy source for plant growth. Supplementary lights are broadly used in agricultural production for the advancement in crop growth, yield, and quality, which has been confirmed by many researchers [13][14][15].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Light is the foremost energy source for plant growth. Supplementary lights are broadly used in agricultural production for the advancement in crop growth, yield, and quality, which has been confirmed by many researchers [13][14][15].…”
Section: Introductionmentioning
confidence: 78%
“…Soluble proteins were extracted with a sodium phosphate buffer and measured calorimetrically using a Bradford Reagent (Sigma-Aldrich, St. Louis, MO, USA), according to Bradford's method [33]. The soluble sugar and starch contents were determined by the Anthrone colorimetric method according to Wei et al [15].…”
Section: Chlorophyll a And B Soluble Protein And Carbohydrate Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce varieties supplemented with short term red light (638 nm) possessed substantial antioxidant capacity, and the effect of supplemental light was variety dependent [9]. However, a long duration of LED lighting can also put plants under stress [197]. The level of accumulation of antioxidants in lettuce leaves is a determinant of the sensitivity of different varieties of lettuce towards supplemental light.…”
Section: Impact Of Leds On Secondary Metabolites Of Plants and Their mentioning
confidence: 99%
“…Wojciechowska et al compared several commonly used artificial light sources in terms of yield and energy consumption and found that mixed LEDs were an effective way to improve production efficiency of Valerianella locusta L. [3]. The authors also have previously investigated the effects of the source, intensity and duration of light on the growth and development of crops, and have come to the conclusion that LEDs are superior to other light sources during the seedling production period of vegetables crops [4][5][6].…”
Section: Introductionmentioning
confidence: 99%